2014
DOI: 10.1371/journal.pone.0093734
|View full text |Cite
|
Sign up to set email alerts
|

Repeat HIV Testing at Voluntary Testing and Counseling Centers in Croatia: Successful HIV Prevention or Failure to Modify Risk Behaviors?

Abstract: HIV testing plays a critical role in preventing the spread of the virus and identifying infected individuals in need of care. Voluntary counseling and testing centers (VCTs) not only conduct testing but they also provide counseling. Since a proportion of people who test negative for HIV on their previous visit will return for retesting, the frequency of retesting and the characteristics of those who retest may provide insights into the efficacy of testing and counseling strategies. In this cross-sectional, ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
3
9
1
Order By: Relevance
“…This has a serious impact on planning and response to the HIV epidemic as resources might be wasted. Contrary to our findings, repeat/multiple testing has been mostly reported in people with prior HIV negative or unknown statuses [ 16 - 20 ]. Secondary and higher levels of education were associated with increasing odds of ever being tested, similar to findings in studies in SSA and Europe [ 16 , 17 , 20 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This has a serious impact on planning and response to the HIV epidemic as resources might be wasted. Contrary to our findings, repeat/multiple testing has been mostly reported in people with prior HIV negative or unknown statuses [ 16 - 20 ]. Secondary and higher levels of education were associated with increasing odds of ever being tested, similar to findings in studies in SSA and Europe [ 16 , 17 , 20 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Sex was not associated with repeat HIV testing in our study as reported by Matković Puljić et al . in Croatia [ 16 ] and Hensen et al in Zambia [ 17 ]. Forty per cent (40%) of people living with HIV are not aware of their HIV-positive status [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The searches yielded 15 004 records after de‐duplication; after full‐text review, 368 studies were included in the overall systematic review (Figure ). Of the 368 studies, 130 are described in this paper, exploring interventions and feasibility of HIV testing in health care settings in Europe, including 84 peer‐reviewed articles and 46 conference proceedings (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…Other testing strategies included routine testing ( n = 32) , provision of HIV testing as a component of an integrated testing programme ( n = 29) , IC testing ( n = 14) and partner notification ( n = 4) . Routine testing was most commonly implemented in hospital departments including emergency departments ( n = 15) , inpatient units ( n = 10) and outpatient departments ( n = 4) .…”
Section: Resultsmentioning
confidence: 99%
“…However, it is interesting to note that the proportion of a previous HIV test is similar between groups, suggesting that both groups may have similar perceived high risk of acquiring HIV. 29 30 …”
Section: Strengths and Limitationsmentioning
confidence: 99%